On the International Effects of Inflation Targeting - Lin, Shu (The Review of Economics and Statistics, 2010)
This study empirically examines the international effects of inflation targeting. Employing a variety of propensity score matching methods, we find strong evidence that inflation targeting has significantly different impacts on exchange rate volatility and international reserves in different country groups. It significantly increases real and nominal exchange rate stability and international reserves in developing countries but lowers them in industrial countries. On average, inflation targeting increases (lowers) reserves roughly by the size of 1.3 (1.8) months of imports values in developing (industrial) countries. The treatment effects on targeting countries' current accounts are found to be insignificant in both country groups.